(untitled) (Texas Journal of Medical Science, 2025)
Disseminated intravascular coagulation (DIC) is a complex pathological condition characterized by uncontrolled activation of the hemostatic system, depletion of coagulation factors, microthrombus formation, and hemorrhagic complications. This article discusses the key mechanisms of DIC pathogenesis, including the role of tissue factor, endothelial dysfunction, and the imbalance between coagulation and fibrinolysis. Modern diagnostic approaches and potential therapeutic strategies are also presented